Plasma Exchange Therapy to Reduce Mortality in Japanese Patients With Diffuse Alveolar Hemorrhage and Microscopic Polyangiitis. Issue 2 (5th August 2019) - Abe, Yoshiyuki; Yamaji, Ken; Endo, Yukari; Kusaoi, Makio; Nakano, Soichiro; Yang, Kwang‐Seok; Tada, Kurisu; Tsuda, Hiroshi; Tamura, Naoto
Abstract: Diffuse alveolar hemorrhage (DAH) is well known as a serious complication of microscopic polyangiitis (MPA). We examined the effectiveness of plasma exchange (PLEX) therapy to reduce mortality in Japanese DAH patients with MPA. This retrospective, double‐center, observational cohort study included 20 DAH patients with MPA who were admitted to Juntendo University Hospital or Juntendo Koto Geriatric Medical Center between April 1998 and March 2018. The primary outcome was non–disease‐specific mortality. The 1‐year survival rate of patients with PLEX therapy ( N = 4) was higher than that of patients with conventional therapy ( N = 16, 75% and 13%, respectively, P = 0.037). Higher values of the 1996 Five‐Factor Score (FFS) and 2009 FFS were associated with increased mortality, with hazard ratios of 2.29 ( P = 0.040) and 2.41 ( P = 0.043), respectively, by Cox univariate analysis. We investigated PLEX therapy for reducing mortality in DAH patients with MPA, and the 1996 FFS and 2009 FFS were both independent prognostic factors.